Respuesta :

[tex]y=x\sin x[/tex]

[tex]\dfrac{\mathrm dy}{\mathrm dx}=x\dfrac{\mathrm d(\sin x)}{\mathrm dx}+\dfrac{\mathrm dx}{\mathrm dx}\sin x=x\cos x+\sin x[/tex]

[tex]\dfrac{\mathrm d^2y}{\mathrm dx^2}=x\dfrac{\mathrm d(\cos x)}{\mathrm dx}+\dfrac{\mathrm dx}{\mathrm dx}\cos x+\dfrac{\mathrm d(\sin x)}{\mathrm dx}[/tex]
[tex]\dfrac{\mathrm d^2y}{\mathrm dx^2}=-x\sin x+\cos x+\cos x[/tex]
[tex]\dfrac{\mathrm d^2y}{\mathrm dx^2}=-x\sin x+2\cos x[/tex]

[tex]\dfrac{\mathrm d^3y}{\mathrm dx^3}=-\left(x\dfrac{\mathrm d(\sin x)}{\mathrm dx}+\dfrac{\mathrm dx}{\mathrm dx}\sin x\right)+2\dfrac{\mathrm d(\cos x)}{\mathrm dx}[/tex]
[tex]\dfrac{\mathrm d^3y}{\mathrm dx^3}=-x\cos x-\sin x-2\sin x[/tex]
[tex]\dfrac{\mathrm d^3y}{\mathrm dx^3}=-x\cos x-3\sin x[/tex]

Substitute the derivatives into the given ODE and check to see if the relation is an identity.

[tex]x\dfrac{\mathrm d^3y}{\mathrm dx^3}+x\dfrac{\mathrm dy}{\mathrm dx}+2y=0[/tex]
[tex]x(-x\cos x-3\sin x)+x(x\cos x+\sin x)+2x\sin x=0[/tex]
[tex]-x^2\cos x-3x\sin x+x^2\cos x+x\sin x+2x\sin x=0[/tex]
[tex]0=0[/tex]

and we're done.